1991
DOI: 10.1007/bf01708406
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative blood cultures for diagnosis and management of catheter-related sepsis in pediatric hematology and oncology patients

Abstract: Paired quantitative blood cultures collected simultaneously via catheter and peripheral vein in Isolator 1.5 ml tubes, were performed in 50 febrile hematology children. Samples were taken to diagnose catheter-related sepsis (CRS) without catheter removal and to monitor the therapeutic efficiency of antimicrobials administered through the infected device by infusion and/or by the antibiotic lock technique (ALT). In 7 children (14%) the colony counts from catheter blood samples were 30-fold higher than the colon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(23 citation statements)
references
References 19 publications
2
20
0
1
Order By: Relevance
“…More than 50% of CVC-related bacteremias were undiagnosed with this method and the ratio was above 30 in four cases of infections unrelated to CVC infection. Douard et al [23] found similar results in a pediatric population. On the other hand, Snydman [20] and Vanhyngen [11] using a semi-quantitative method, and Mosca [21] using a quantitative method were nearly 100% accurate in predicting CVC-related bacteremia.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…More than 50% of CVC-related bacteremias were undiagnosed with this method and the ratio was above 30 in four cases of infections unrelated to CVC infection. Douard et al [23] found similar results in a pediatric population. On the other hand, Snydman [20] and Vanhyngen [11] using a semi-quantitative method, and Mosca [21] using a quantitative method were nearly 100% accurate in predicting CVC-related bacteremia.…”
Section: Discussionsupporting
confidence: 74%
“…Since the reinsertion of a new CVC can be hazardous and some CVC-related infection may be treated without CVC removal [12], several studies have sought a way of predicting catheter colonization without removing the CVC. Three main techniques have been evaluated: skin cultures at the CVC insertion point, hub cultures of the CVC [13][14][15][16][17][18][19] and quantitative or semi-quantitative blood cultures collected simultaneously via CVC and peripheral vein [11,[20][21][22][23]. The contribution of skin and hub cultures towards the diagnosis of catheter colonization has been variable among these different studies.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, quantitative blood cultures were used to help elucidate the true source of infection. There are many methods of interpretation, but in general, a blood culture drawn from a central line that grows Ͼ100 CFU/ml bacteria or has a colony count that is 3-to 5-fold greater than a paired peripheral blood draw was indicative of a catheter-associated bloodstream infection (28)(29)(30).…”
Section: Blood Culture Collectionmentioning
confidence: 99%
“…Although quantitative blood cultures (QBC) collected simultaneously through a CVC and peripheral venipuncture (PV) have been used for the diagnosis of catheter-related bloodstream infections (3,6,14), the usefulness of QBC collected through CVC for the diagnosis of bacteremia from any source has not been thoroughly investigated.…”
mentioning
confidence: 99%